2019
DOI: 10.1097/coh.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

Germinal centers B-cell reaction and T follicular helper cells in response to HIV-1 infection

Abstract: Purpose of the review: This review aims to summarize the recent findings on germinal centers (GCs) B-cell reaction and Tfh cells in HIV-1 infection, with particular emphasis on the spatial organization of the GC, follicular cell regulation, and cellular alterations resulting from HIV infection. Recent findings: HIV-specific bNAbs are generated by iterative cycles of B cell maturation supported by GC environment. Recent observations underline that GC structural alterations at the earliest stages of HIV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Our study found that the S-RBD-IgG antibody seropositivity rates and antibody levels were lower in PLWH at 28 ± 7 days after two doses of the BBIBP-CorV vaccine or the CoronaVac vaccine than in the HCs, which was consistent with the findings of previous studies [7][8][9]. The structural alterations in the germinal center of PLWH may affect T follicular helper cell and germinal center B cell homeostasis, thereby preventing the elevation of effective humoral immunity [10]. Therefore, humoral immune responses between PLWH and healthy individuals are generally comparable.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that the S-RBD-IgG antibody seropositivity rates and antibody levels were lower in PLWH at 28 ± 7 days after two doses of the BBIBP-CorV vaccine or the CoronaVac vaccine than in the HCs, which was consistent with the findings of previous studies [7][8][9]. The structural alterations in the germinal center of PLWH may affect T follicular helper cell and germinal center B cell homeostasis, thereby preventing the elevation of effective humoral immunity [10]. Therefore, humoral immune responses between PLWH and healthy individuals are generally comparable.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, CD4 + T cells, especially T-follicular helper (Tfh) cells, are required for the induction of high-affinity antibody responses and the formation of longlived B cell memory. The structural changes in the germinal center and functionally altered Tfh cells derived by HIV replication and the consequent impaired interaction between Tfh cells and germinal center B cells might contribute to impaired immune response [36,37]. In addition, a third booster shot of a COVID-19 vaccine was reported to potentially provide more protection in the general population [38].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry-based studies helped to establish the idea that CD4 + T cell activation and exhaustion was mostly related to the ongoing infection surrounding germinal centres [ 46–48 ]. Thus, a latent HIV-1 infection during the transition of activated T cells to memory T cells could lead to establishment of latently infected CD4 + T cell populations, mostly within the T cell zones surrounding the HIV-1-specific germinal centres [ 49 ]. Density of these proliferating T cells surrounding the HIV-1-specific germinal centres may focus replication to these T cell zones and reduce HIV-1 migration/diffusion into other antigen-specific germinal centres [ 31 ].…”
Section: Discussionmentioning
confidence: 99%